Structure/activity of PtII/N,N-Disubstituted-N’-acylthiourea complexes: Anti-tumor and anti-mycobacterium tuberculosis activities - Plutín, Ana M.; Alvarez, Anislay; Mocelo, Raúl; Ramos, Raúl; Sánchez, Osmar C.; Castellano, Eduardo E.; da Silva, Monize M.; Villarreal, Wilmer; Colina-Vegas, Legna; Pavan, Fernando R. [UNESP]; Batista, Alzir A. (Sociedade Brasileira de Quimica (SBQ), 2018)
The syntheses, characterization, cytotoxicity against tumor cells and anti-Mycobacterium tuberculosis activity assays of PtII/PPh3/N,N-disubstituted-N’-acylthioureas complexes with general formulae [Pt(PPh3)2(L)]PF6, PPh3 = triphenylphosphine; L = N,N-disubstituted-N’-acylthiourea, are here reported. The complexes were characterized by elemental analysis, molar conductivity, infrared (IR), nuclear magnetic resonance (NMR) (1H, 13C{1H} and 31P{1H}) spectroscopy. The 31P{1H} NMR data are consistent with the presence of two PPh3 ligands cis to each other position, and one N,N-disubstituted-N’-acylthiourea coordinated to the metal through O and S, in a chelate form. The structures of the complexes were determined by X-ray crystallography, forming distorted square-planar structures. The complexes were tested in human cell lines carcinomas and also screened with respect to their anti-Mycobacterium tuberculosis activity (H37RvATCC 27294). It was found that complexes with N,N-disubstituted-N’-acylthiourea containing open and small chains as R2 groups show higher cytotoxic and higher anti-Mycobacterium tuberculosis activity than those containing rings in this position.
Keywords: Mycobacterium tuberculosis; Platinum(II); Tumor cells